A Randomised Control Trial in High-Risk Children of Depressed and Anxious Individuals to Prevent Mood and Anxiety Problems in Youth - Ayesha Umer, Tehreem Zahra, Afra Mirza, Bazla Naseer Hashmi, Nazish Naeem, Inshaal Nasir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A great burden is placed on patients by the increased rate of being anxious and mood abnormalities. In this group, there is a clear need to halt the prevention of psychopathology because their offspring are more likely to have these diseases themselves. Due to the substantial coexisting disorders, preventative programs should concentrate on both anxiety and depression. Furthermore, although increased sensations are frequently a sign of preventive actions, resilience-based prevention programs may also be advantageous for children with other high risk profiles. Method: A randomized control clinical trial is used in the current study. It is designed for high-risk people who are symptomless as well as those who have sub-syndrome symptoms. Two among the criteria of the High Risk are met by individuals who do not exhibit any symptoms (attempt). Among a previous study, this measure was created, and it correlates with a higher risk in children of depressed individuals. Children between the ages of 8 and 17 (n = 204) who exhibit sub threshold symptoms or who meet the requirements on the HRI are randomly assigned to either (a) 10 sessions every week for child with CBT (b) limited information.. The main result is when a child's anxiety or mood condition first manifests itself. Secondary end factors include the number of days spent feeling depressed or anxious, the severity of symptoms in children and parents, living quality and financial efficiency. Researchers has chosen coping, parent-child relationship, personal attachments , optimism/pessimism, therapies, and emotion processing as potential mediators of treatment outcome based on the etiology of mood and anxiety disorders as well as processes of change during therapies. Results: The happy and Negative Affect Schedule (PANAS) is a 20-item self-report scale used to assess both happy and negative affect. Positive and negative affect both reflect dispositional characteristics; high negative affect is characterised by unpleasant engagement and subjective distress, whereas low NA is characterised by the lack of these feelings. PA, on the other hand, is a measure of how much an adult enjoys engaging with their surroundings. The Attentional Breadth Task, a computer task that was preprogrammed in e-prime, was also used to measure mother-child attachment. The task is based on the supposition that persons with insecure attachment may process information differently when it comes to data that is pertinent to attachments, Practical Implication: Using a quick and focused intervention aimed at strengthening the family unit, the present intervention trial seeks to drastically lower the chance of passing mood and anxiety disorders down the generations and resiliency in youngsters who could be at risk. We intend to determine the mechanisms of change and assess the efficacy and the intervention's efficacy and cost. Conclusion: Positive and negative affect both reflect dispositional features, according to the study's findings. High negative affect is marked by subjective anguish and unpleasant engagement, whereas low negative affect is marked by the absence of these emotions. Keywords: Anxiety, Mood disorders, Depressed, Youth, teenagers, Pakistan